The Evolution of Competence Research in the International Context - Sabelnikova E.V (Moscow State University of Psychology and Education, 2021)
The article presents the history of the development of competence assessment from the XX century till now. On the basis of the completed study the author developed the periodisation of national and international research projects in order to systematize various projects and highlight the stages of their development. The main focus of most projects is the assessment of competences and skills, literacy, respondents' socio-demographic characteristics. All these components allow to analyse the received data as full as possible. The recent showed studies focus on the ability of using the existing skills and competences in real-life situations. The abovementioned periodisation gives an opportunity to researchers to obtain structured information of the projects and use it in their own research.